A systematic review about precision technologies for livestock production and their application in different stages of poultry farming - Gonzalez, Joseph; Villarreal, Vladimir; Munoz, Lilia; Pardo, Cesar (2022 V Congreso Internacional en Inteligencia Ambiental, Ingeniería de Software y Salud Electrónica y Móvil (AmITIC), 2022)
Precision Livestock Farming (PLF) technologies correspond to the deployment of electronic devices and digital tools to manage livestock production efficiently. This systematic review compiles the results of review studies on the use of PLF technologies in poultry farming, synthesizing the report of factors such as the technologies used, their application context, study subjects, production stages evaluated, challenges encountered and future opportunities. For this, a study search strategy applied in 8 academic databases was designed within the framework established by the definition of eligibility criteria and the application of quality assessment tools of the studies found. As a result, 13 studies were included: 2 systematic reviews and 11 narratives reviews. The application of optical technologies was reported in all 13 studies, followed the use of sensors in 7 studies (biosensors, wearable and/or environmental sensors), the analysis of sounds captured by microphones in 4 studies, and the use of autonomous agricultural robots in 2 of them. In addition, 4 studies considered the application of PLF technologies in the egg handling stage, 9 in the poultry rearing stage and 4 in the meat processing stage. It is concluded that there is a need to deepen the research on the application of PLF technologies of a commercial nature in real poultry production contexts, involving producers to determine those implementations that add greater value to their business.